Luke: I. H. Marshall and Historical Redaction - Blomberg, Craig L. (The Evangelical quarterly, 2022)
I. Howard Marshall broke fresh ground with his Luke: Historian and Theologian in 1970 when the reigning critical methodology was a form of redaction criticism that largely assumed that theology and history were mutually exclusive. Not only did Marshall contest this assumption but he stressed that a historian was as good as his sources, and Luke had good ones. A half-century later, scholarship has significantly progressed, with Marshall’s views having left an important legacy. Multiple critical tools may be combined. Theology and history can work in tandem. Redaction criticism need not be antithetical to the historical reliability of a Gospel.